Ultrasonic testing of heat damaged composite materials - Thoo, Kah Kian (2016)
Composite in present day is utilized in a variety of industries, namely Automation to Aerospace industries. Pushing the material’s properties to its limits, it is unknown to many how heat delamination can affect the mechanical properties such as strength and fatigue failure of composite. This report will further look into the effects on how heat can cause delamination on composite material. Knowing heat damage could be easily spotted only when composite materials are badly heated. Therefore, the use of different types of Non-Destructive Testing (NDT) such as Visual Inspection, Ultrasonic testing and Fourier Transform mid-Infrared (FTIR) techniques would be used to detect heat damages on composite materials. In this study, Carbon Fibre Reinforced Polymer (CFRP) composite will be utilized to test the severity of heat damage when heated, tests will be conducted by Visual Inspection, Ultrasonic C-scan and FTIR techniques and the same specimen would be reheated again and these cycles continues for 3 times. The specimens will be heated at different temperatures ranging from 100℃ to 350℃ by a heat gun with a time frame of 30 minutes each. Ultrasonic testing and FTIR will be conducted on the specimens to gather results to determine the extent of damage that had occurred on the Carbon Fibre Reinforced Polymer (CFRP) Specimens during the process of heating. The purpose of this report is to determine how much internal damage had been done to the specimens which cannot be visually determined. It will also determine the advantages and disadvantages of Visual Inspection, Ultrasonic testing “C-Scan” and FTIR.